2013
DOI: 10.1038/jid.2013.86
|View full text |Cite
|
Sign up to set email alerts
|

SOCS1 Prevents Potentially Skin-Reactive Cytotoxic T Lymphocytes from Gaining the Ability to Cause Inflammatory Lesions

Abstract: Suppressor of cytokine signaling 1 (SOCS1) is a critical regulator of T lymphocyte homeostasis. SOCS1-deficient mice accumulate CD8(+) T cells, which display a memory-like phenotype and proliferate strongly to IL-15. Socs1(-/-) mice develop inflammatory skin lesions, however, the underlying mechanisms are not well understood. In order to investigate the role of SOCS1 in regulating CD8(+) T cells potentially reactive to tissue antigens (Ags) of the skin, we generated Socs1(-/-) mice expressing MHC-I-restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Rodriguez et al demonstrated that suppressor of cytokine signaling1 ( Socs1) −/− MHC-I-restricted premelanosome protein-1 (Pmel-1) transgenic TCR CD8 + T cells expressed higher levels of Blimp-1 upon stimulation with cognate self-antigen (mgp10025–33) than did wild type Pmel-1 cells, suggesting that SOCS1 regulates Blimp-1. However, the underlying mechanism of this effect is unknown [99]. Kurachi et al demonstrated that a basic leucine zipper transcription factor (BATF) is essential for operation of the differentiation checkpoint in early effector CD8 + T cells.…”
Section: Transcriptional Regulation Of Blimp-1 In T Cellsmentioning
confidence: 99%
“…Rodriguez et al demonstrated that suppressor of cytokine signaling1 ( Socs1) −/− MHC-I-restricted premelanosome protein-1 (Pmel-1) transgenic TCR CD8 + T cells expressed higher levels of Blimp-1 upon stimulation with cognate self-antigen (mgp10025–33) than did wild type Pmel-1 cells, suggesting that SOCS1 regulates Blimp-1. However, the underlying mechanism of this effect is unknown [99]. Kurachi et al demonstrated that a basic leucine zipper transcription factor (BATF) is essential for operation of the differentiation checkpoint in early effector CD8 + T cells.…”
Section: Transcriptional Regulation Of Blimp-1 In T Cellsmentioning
confidence: 99%
“…Moreover, pmel-1 mice have been increasingly employed to study autoimmune vitiligo [7], [60][64] and uveitis [61], [63], [65]. The pmel-1 mouse was generated using two transgenic vectors, which contained variable domains of the endogenous TCR as described previously [7] (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that differential expression of UCHL1 was majorly involved in the proliferation and differentiation of T cells, including CD8 memory CTLp, circulating TCR-gamma/delta+ lymphocytes, and mature T cells [ 59 ]. SOCS1 has been identified as an inhibitor against cytokine release and a growth factor receptor, it plays a crucial role in regulating T cell homeostasis, development, and homeostasis activation [ 60 64 ]. However, the function of OSTM1, PCGF2, PSMD2, and USP54 have not been investigated in the antitumoral immune response.…”
Section: Discussionmentioning
confidence: 99%